Detection of mouth alcohol during breath alcohol analysis. (April 2015) - Lindberg, Lars; Grubb, David; Dencker, Daniel; Finnhult, Mikael; Olsson, Sven-Gunnar
Highlights: A method to detect mouth alcohol is proposed. Alcohol and water in simultaneously exhaled breath volumes were studied. Mouth alcohol accompanies exhaled water vapor from the oral cavity. The accuracy to use exhaled water vapor to detect mouth alcohol was determined. The method was practical and detected mouth alcohol with high reliability. Abstract: The presence of mouth alcohol (MA) during alcohol breath test for law enforcement is the most common cause of falsely high breath alcohol concentrations (BrAC). A fast and reliable test for detection of MA roadside at the scene of the act would facilitate the police efforts for proper prosecution. A tentative technique to use orally exhaled water vapour as a reference gas to position the origin of alcohol was validated. BrAC and water vapour concentration (WVC) were simultaneously measured as a known MA component was added to subjects with existing blood alcohol. In the absence of MA, water always precedes alcohol in a volumetric expirogram. In the presence of MA this relationship reversed. A scatterplot of WVC versus BrAC from similar fractional exhaled volumes illustrates how their relative positions change by MA. A deviation area (DA) between the scatterplot curve and a fictitious linear relationship was defined as a measurement of MA. The accuracy and cut-off level of the DA to detect MA were determined with receiver operating characteristic (ROC) curve analysis. The area under the ROC curve (AUC) was 0.95 (95% CI 0.90–1.0), indicating excellent discriminatory ability. The optimal cut-off for DA to discriminate between MA ≥0.010 mg/L (1 μg/100 ml, 0.002 g/210 L) or lack of MA was −0.35, with a sensitivity of 0.91 and specificity of 0.95. Analysis of BrAC in relation to WVC is a practical method to detect and confirm MA contamination with high reliability.